Religious reality in short stories with the theme of the COVID-19 pandemic - Ulya, Chafit; Suwandi, Sarwiji; Wardani, Nugraheni Eko; Setiyoningsih, Titi; Putri, Ulfa Rizqi; Liliani, Else (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2024)
During the COVID-19 pandemic, short story literary works emerged with the theme of the pandemic. This short story raises the theme of the pandemic and, at the same time, provides an overview of the religious realities that occurred during the pandemic. The pandemic creates new problems at the level of the religious habits. This is a dilemma faced by the Indonesian people. The reality of religion during the pandemic can be seen in the rituals of worship and religious habits. This research aims to describe the reality of religion during the pandemic in short stories with the theme of the COVID-19 pandemic. The data source in this research is nine short stories with the theme of the COVID-19 pandemic published in online media (suaramerdeka.com, republika.com, and cerpenmu.com) in the period 2020-2021. The selection of the nine short stories was based on a purposive sampling technique with a focus on novice writers. The technique used in this research is note-taking, which involves the writer reading and recording the findings of religious realities in short stories with the theme of the COVID-19 pandemic. The results of this research show two aspects of religious reality in short stories with the theme of the COVID-19 pandemic, namely worship rituals and religious habits. The reality of religion in worship rituals in short stories with the theme of the COVID-19 pandemic is to invite people to use religion to resolve the pandemic without worsening conditions. Meanwhile, the reality of religious diversity in religious habits shows the phenomenon of people still trying to realize religious habits during Eid by paying attention to the health protocols that apply amid the COVID-19 pandemic.